A new species of Spigelia (Loganiaceae) from Guerrero, Mexico - Alvarado-Cárdenas, Leonardo Osvaldo; Jiménez, Jaime (Phytotaxa, 2015)
A new species of Spigelia endemic to Guerrero, Mexico, is described and illustrated. Spigelia guerrerensis sp. nov. can be separated from all known species of the genus by its infundibuliform white corollas sometimes tinged with purple at the lobe margins and in the base of the throat, apically hirsutulose fruits, and its restriction to the mountain system of northeastern Guerrero. In addition, we provide a distribution map and conservation status recommendation for the new species, as well as a key to the species of Spigelia known from Guerrero. Including this new addition, 17 species are recognized in Mexico, making it one of the hotspots of the genus.